DAMPAK IMPOR TERHADAP PRODUKSI KEDELAI NASIONAL - Zakiah Zakiah (Jurnal Agrisep, 2011)
Import of Soybean and Its Impact on National ProductionABSTRACT. This study examine import affect on soybean production in Indonesia. The study uses yearly data and simultan equation model is employed in this study. The result show that soybean price, corn price, fertilizer price and lag harvest area significant to soybean harvest area. Fertilizer price, technology lag productivity significant to soybean productivity. Production, impor, price impor, demand of soybean and lag soybean price significant to soybean price. Harvest area more response to corn price and fertilizer price than farmers soybean price and lag harvest area. Farmers soybean price more response to production, impor and demand of soybean. So impor may decrease soybean price in long run decrease national soybean production. Needed transfer teknologi, subsidi, distribution and good price to increase national soybean production.